Assessment of groundwater quality and irrigation suitability for crop production using hydrochemical parameters in a coastal region of Tamil Nadu, India - Kaviyazhagan, S; Gurusamy, A; Subramanian, E; Prabhaharan, J; Amutha, R; Sivasankari, B; Sathishkumar, A; Sourav, K K (Plant Science Today, 2025)
Quality irrigation water is essential in semi-arid and coastal regions for sustainable crop production. The quality of irrigation water has deteriorated nowadays due to indiscriminate use of chemical fertilizers and overexploitation of groundwater. Therefore, the study assessed groundwater quality of the Nainarkoil block of Ramanathapuram district, Tamil Nadu, where agriculture is the predominant economic activity. A total of 50 geocoded samples were collected and analysed for hydrochemical parameters, including pH, electrical conductivity (EC), major cations (sodium (Na+), potassium (K+), calcium (Ca2+) and magnesium (Mg2+)) and anions like (CO32-, HCO3-, Cl-, SO42). Irrigation quality indices like sodium percentage, Kelly's Index, sodium adsorption ratio, permeability index and residual sodium carbonate were computed to determine overall suitability for irrigation. The Geographic Information System tool ArcGIS was employed to create a spatial distribution map of quality parameters, which offers a clear visual representation of groundwater characteristics. The results revealed wide variations in suitability with several locations exhibiting elevated salinity and hardness. Eighty percent of samples exceeded the allowable limits for pH and EC respectively. Where 56 % and 64 % of locations had Ca2+ and Mg2+ concentrations respectively, above the limit. Na+ and K2+ ions surpassed the limits of WHO in 78 % and 26 % of samples respectively. Regarding anions, 76 %, 54 % and 68 % of the samples crossed the limits for CO3+, HCO3+ and Cl- respectively. According to the findings, the majority of groundwater samples exceeded the WHO’s standard limits, which are not appropriate for irrigation, crop production and findings highlight the need for regular monitoring and sustainable water management practices.